Political Cuteness! Charting News Narratives of China’s Panda Diplomacy in Recipient Countries of Australia, Scotland and Canada - Zheng, Hanze (Auckland University of Technology, 2017)
Panda diplomacy is a unique animal diplomacy practice of China yet it has received little academic attention and seldom dissected in the literature. This research quantitatively measures and qualitatively analyses the achievement of this diplomacy practice reflected in the local news production regarding the panda in three select panda host countries (Scotland, Canada and Australia), and charts narratives of concurrent events corresponding to each panda loan deal with information extracted from the news content. Journalism terms such as news values, framing, and narrative theory are used as theoretical tools to examine the news content to understand the influence the journalistic process exerts on the mental association formed among the readership regarding the panda. Findings of this study suggest that while the panda is perceived to have a wide range of news values by the media outlets of all three studied countries, the portrayal of the image of the animal as well as the levels of success of the panda diplomacy varies significantly. Scotland shows a high level of diplomatic achievement, with unanimous recognition of the political value of the panda as a goodwill ambassador from the Scottish media, public and government. In the case of Canada, while the journalists hold sceptical views towards the symbolic values of the panda in the development of the Sino-Canada relationship, the cuteness of the image of the panda was nevertheless portrayed, separately from the political dimension. Finally, Australian media outlets demonstrate the least amount of enthusiasm in the panda, yet a critical concern was kept in the journalistic focus on the economic dimension of the loaned animal. The data coding method designed for the research may be applicable for analysts of journalism when investigating news content in terms of the frames, tones and viewpoints employed in the journalist process that are intended to exert an influence on the perception and ideas formed among the readership in regards to the news subjects. The narratives charted from the data provide diplomacy practitioners with insights for use in adjusting public diplomacy activities in order to generate enhanced publicity.
Keywords: Soft power; Public diplomacy; Panda diplomacy; Animal diplomacy; Mediated diplomacy; Mass media; News value; Framing; Narratives; Hard & soft news; The chain in news communication